Coming Closer to Citizens? Frustrated Dialogue on the Danish Health Authority's Facebook Page During COVID-19 - Madvig, Fie; Achiam, Marianne; Adler-Nissen, Rebecca; Johansen, Nicklas; Whiteley, Louise (Frontiers in Communication, 2022)
As the COVID-19 pandemic began, health authorities rushed to use social media to communicate information and persuade citizens to follow guidelines. Yet a desire to ‘come closer to citizens’ often came into conflict with the very consequences of doing so – many social media interactions were characterized by complaint, resistance, trolling or misinformation. This paper presents a case study of the Danish Health Authority’s (DHA) Facebook page, focusing on the initial phase of the pandemic and on posts about face masks. Face masks were chosen as an exemplar of the many topics where scientific research was being communicated as it unfolded, and where relations between science, policy, and politics were also evolving in public. In other words, topics where what should be communicated and why was unclear and unstable, both for health authorities and for citizens who wished to engage with them. A qualitative thematic analysis of the DHA Facebook page, grounded in the practice-based knowledge of one of the authors and regular feedback meetings with DHA staff, unpicks what kinds of engagements between authority and citizens occurred. The analysis particularly looks for dialogue – as a mode of communication implicitly promised by social media platforms, and as a well-established ingredient of trust in relationships between experts and citizens. Drawing on Grudin’s definition of dialogue as ‘reciprocal and strange’, we argue that the DHA’s Facebook policy inhibited such encounters, in part by practical necessity, and in part due to a reluctance to discuss the entanglements between health guidelines and politics. But we also identify ‘strangeness’ in the apparent disconnect between individual engagements and collective responses; and ‘reciprocity’ in the sharing of affect and alternative forms of expertise. We also highlight the invisible majority of silent engagements with DHA information on the Facebook page, and ask whether the visibly failed dialogue that ran alongside was a price worth paying. The paper also serves as an example of qualitative research situated within ongoing practice, and as such we argue for the virtue of these more local, processual forms of evidence-based science communication.